Internal audit function, audit competence and organisational perform ance of selected public agencies in Uganda - Busobozi, Ahmed (Kampala, 2016)
Unpublished dissertation (MSc. ACC. & FIN.) - Makerere University, 2 016.
Includes bibliographical references (p. 31-34).
Keywords: Government business enterprises -- Auditing